Making use of coastal wave energy: a proposal to improve oscillating water column converters (2014)
This paper aims to describe an alternative design (protected by patent), for an onshore wave based energy converter, specifically an oscillating water column, capable of providing increased efficiency. In order to compare the various alternative designs, a theoretical model that describes the physical behavior with certain restrictions is proposed. The converters incorporate a rectifying barrier leading to a large pool of water between the sea and the converter. In order to estimate the theoretical increase in achievable power, a theoretic cycle model is assumed for the simulation of its operational dynamics using a simplified ideal behavior: regular waves, the air assumed to be an ideal gas, with adiabatic compression and expansion. The results obtained show that a correct adjustment of the turbine differential pressure contributes to an increase in the available power output. We conclude that the proposed innovations can lead to an improved technology applicable to this type of converters